1992
DOI: 10.1291/hypres.15.85
|View full text |Cite
|
Sign up to set email alerts
|

Renal .ALPHA.2-Adrenoceptor Overexpression in Dahl Salt-Sensitive Rats. Regulation by Dietary NaCl and Dissociation from Salt-Insensitive Hypertension.

Abstract: Dietary NaCI-induced changes in blood pressure and agonist and antagonist binding properties to renal a2-adrenoceptors were studied in inbred (Rapp) strains of Dahl salt-sensitive (S) and salt-resistant (R) rats. S and R rats were placed on either salt-deficient (0.13% NaCI in chow) or high salt (1% NaCI solution to drink plus 0.13% NaCI chow) diets for 1 to 8 weeks. Saturation binding studies with [3H]-rauwolscine and [H]-p-aminoclonidine and competition studies with [3H]-rauwolscine and epinephrine were then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Furthermore, renal a 2 -adrenergic receptors can be upregulated or downregulated by hormones, 25 denervation, 33 and dietary salt intake. 9 Thus, an SHR female kidney may become functionally a male kidney in terms of blood pressure regulation and renal a 2 -adrenergic receptor expression when put in a male environment. During the 10-day period after transplantation, the female kidneys have enough time to functionally become male kidneys in the studies of Harrap et al 31 a 2 -Adrenergic receptors can be regenerated in only 3 days after being destroyed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, renal a 2 -adrenergic receptors can be upregulated or downregulated by hormones, 25 denervation, 33 and dietary salt intake. 9 Thus, an SHR female kidney may become functionally a male kidney in terms of blood pressure regulation and renal a 2 -adrenergic receptor expression when put in a male environment. During the 10-day period after transplantation, the female kidneys have enough time to functionally become male kidneys in the studies of Harrap et al 31 a 2 -Adrenergic receptors can be regenerated in only 3 days after being destroyed.…”
Section: Discussionmentioning
confidence: 99%
“…9 Each frozen kidney was thawed, decapsulated, weighed, and homogenized in 20 mL ice-cold 50 mmol/L Tris-HCl buffer containing 5 mmol/L EDTA pH 7.7. The homogenate was centrifuged at 1700 rpm for 10 minutes (A500 rotor, Du Pont).…”
Section: Membrane Preparation For Oj-adrenergic Receptor Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that the density of renal a2-adrenoceptors is increased in several genetically hypertensive rat models and high salt feeding further increases the density of the a2-adrenoceptors, paralleled by an increment in blood 7). Recently, studies in our laboratory suggested that the increase in the density of renal a2-adrenoceptors in Dahl salt-sensitive (S) rats ingesting a high salt diet was due to proportional increases both in the high and low affinity binding sites (20).The percentage of high affinity binding sites did not change with strain, sodium content in the diets or whether it was measured by a full agonist or a partial agonist binding (20). Therefore, the extra a2-adrenoceptors produced in S rats are expected to be fully functional.…”
Section: Discussionmentioning
confidence: 99%